2018
DOI: 10.3390/ijerph15122866
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Environmental Tobacco Smoke and Early Development of Children in Rural Guizhou Province, China

Abstract: Background: There is a substantial body of evidence supporting the association between maternal active smoking during pregnancy and child development, but the association between prenatal exposure to environmental tobacco smoke (ETS) and early child development has not been well documented. This cross-sectional study examines the association between prenatal exposure to ETS and the development of children in their first two years of life. Methods: We interviewed the primary caregivers of 446 children under two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
4
13
0
Order By: Relevance
“…Although we did not survey rates of active and passive smoking among our sample, previous studies have shown that in rural China, rates of smoking among men are much higher than among women (59% compared to 2%), suggesting that the majority of tobacco exposure in our sample may be due to secondhand smoke [ 21 ]. This is corroborated by past studies which have found that about 60% of rural mothers are exposed to secondhand smoke during pregnancy [ 26 ]. These findings suggest a lack of knowledge regarding the dangers of tobacco exposure during pregnancy, despite the substantial body of literature linking prenatal tobacco exposure to poor outcomes at birth and in childhood [ 7 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Although we did not survey rates of active and passive smoking among our sample, previous studies have shown that in rural China, rates of smoking among men are much higher than among women (59% compared to 2%), suggesting that the majority of tobacco exposure in our sample may be due to secondhand smoke [ 21 ]. This is corroborated by past studies which have found that about 60% of rural mothers are exposed to secondhand smoke during pregnancy [ 26 ]. These findings suggest a lack of knowledge regarding the dangers of tobacco exposure during pregnancy, despite the substantial body of literature linking prenatal tobacco exposure to poor outcomes at birth and in childhood [ 7 , 55 , 56 ].…”
Section: Discussionsupporting
confidence: 83%
“…Given the significant relationship between maternal education and health behaviors, policy makers and practitioners should develop maternal health education campaigns, focusing on nutrition and tobacco exposure during pregnancy, to improve maternal and fetal health in utero. He [26] Román [55] Hernández-Martínez [7] Rodriguez [62] Alcohol consumption Affects child brain development, damages selective brain structures, and increases the risk of growth retardation; Mothers who consumed alcohol during pregnancy were also at elevated risk of experiencing placental abruption…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of prenatal smoking in France and Iceland were considerably higher than the 1.5% and 0.7% of the current cohort that self-reported smoking before and during pregnancy, respectively. In summary, our study revealed that more than a third of pregnant women from the Emirati population were exposed to ETS, which is lower than China (60.5%) [ 33 ] and France (43.0%) [ 31 ], but higher than the United States (23.0%) [ 30 ].…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have investigated the association between PTE and PAE and neurodevelopment and related disorders [51][52][53] . One study (N=446) conducted in a rural region of China in children with an average age of 15 months found that prenatal exposure to tobacco smoke was associated with neurodevelopmental delay in the cognitive and language domains, assessed using the BSID-III 54 . While we did find evidence of an association between PTE and cognitive development, associations with language development were not statistically significant, although it may be difficult to detect language differences as early as 6 months 41,55 .…”
Section: Discussionmentioning
confidence: 99%